Corporate Governance and Internationalization of Malaysia Public Listed Companies - Lee, Lian Yee; Chu, Ei Yet (School of Social Sciences, USM, 2017)
The main purpose of this study is to examine the impact of the corporate governance on Internationalization for a sample 46 listed companies from 2008 to 2011 which have the reported international operations abroad. The study proposes that corporate governance mechanisms such as directors’ compensation and characteristics of the board could influence firms' decision to internationalization. The measurement for internationalization is foreign sales (FS) and foreign assets (FA). The empirical results indicate that Internationalization by measuring FS is negative and significant related to board size. While measuring by FA indicate the negative and insignificant result. On the other hand, FA and FS are positive and significant related to executive compensation. However, it also found insignificantly related to CEO duality and board independent. According to MCCG requirement, the role of CEO and chairman should remain as non-duality to avoid CEO overpower and board to consist of 1/3 of independent board directors. As result, corporate governance characteristics especially board size and director remuneration does influence firm internationalization.